Clinical researchHyponatraemia in cases of children with pneumonia - Sakellaropoulou, Afroditi; Hatzistilianou, Maria; Eboriadou, Maria; Athanasiadou-Piperopoulou, Fanni (Archives of Medical Science, 2010)
Introduction: Hyponatraemia is the most common electrolyte imbalance seen in clinical practice, and a common laboratory finding in children with community-acquired pneumonia (CAP). This study aimed to identify the incidence of hyponatraemia in cases of CAP, to find predictive tools in order to classify the severity and outcome of CAP and to explore possible differences of clinical importance between the two sexes. Material and methods: The medical files of 54 children (66.4% males), 4.67 ±2.88 years old, were retro-prospectively reviewed. Results: 35/54 (64.8%) children with pneumonia had normal values of sodium at admission, 18/54 (33.3%) had mild hyponatraemia and 1 child (1.9%) moderate hyponatraemia. Increased heart rhythm and tachypnoea at admission were correlated with lower values of sodium (z = –2.664, p = 0.007 and z = –1.705, p = 0.089 respectively). No differences were found between the two sexes concerning the characteristics of pneumonia or the range of sodium in serum at admission. A correlation was found between sodium admission values and: a) C-reactive protein (p = 0.000), and b) leukocyte count (p = 0.006). Sedimentation rate (p = 0.021) was also considered as a possible risk factor affecting the value of sodium at admission to hospital. Finally, a negative association was also observed between the degree of hyponatraemia and the duration of hospitalization (z = –3.398, p = 0.001). Conclusions: Although studies in larger population groups are needed, in our study increased heart rhythm, tachypnoea, leucocyte count, C-reactive protein, and also erythrocyte sedimentation rate could be considered as possible risk factors influencing the degree of hyponatraemia, and thus the outcome of hospitalized children with CAP.